Finite element model-based evaluation of the effectiveness of the incisional skinbridge procedure for posterior horseshoe perianal abscess - Shi Rong; Wang Jing; Ke Minhui; Chen Zuqing; Huang Juan; Chen Riqi; Wang Zhaochu (结直肠肛门外科)
[Objectives] To evaluate the effectiveness of the incisional skin-bridge procedure in the treatment of posterior horseshoe perianal abscess based on finite element model. [Methods] A cohort of 120 patients with posterior horseshoe perianal abscess who underwent the incisional skin-bridge procedure in the Department of Anorectal Surgery, Affiliated People’s Hospital of Fujian Traditional Chinese Medicine University (Fujian People’s Hospital) from September 2020 to December 2022 were included. These patients were randomly assigned into either standard skin-bridge group or the wide skin-bridge group (60 patients each) using random number table. Three-dimensional finite element model for both the standard skin-bridge (model A) and wide skin-bridge (model B) were constructed. Stress and displacement metrics at various skin-bridge nodes during surgery were quantified and incorporated into their respective models. Six pivotal nodes were selected for model validation, followed by comparisons of displacement disparities between the two models and an evaluation of anal pressure three months post-surgery. [Results] Displacements measured surgically at 174 nodes in the standard skin-bridge group and 173 nodes in the wide skin-bridge group significantly deviated from the model prediction (P<0.05), whereas other nodes displacements measured surgically aligned with the model (P>0.05). Compared to model B, nodes 89, 173, and 257 located on model A’s inner skin-bridge edge showed markedly less displacements (P<0.05), while nodes 90 and 258 on the outer edge exhibited increased greater displacements (P<0.05). Inner edge displacements were substantially greater than those at the outer edge in both models (P<0.05). Postoperative three-month anal pressure revealed that the anal resting pressure and maximal contraction pressure of the standard skin-bridge group surpassed those of the wide skin-bridge group (P<0.001). [Conclusion] The finite element method efficaciously mirrors the biomechanical dynamics of incision and skin-bridge procedures for perianal abscesses. During surgery, the skin-bridge nodes endure varied tensile forces. Tailoring the skin-bridge design might be crucial in preserving postoperative anal integrity and functionality following perianal abscess surgery.